The Spiritual Dimension in Islamic Da’wah and Building Social Piety among Gorontalo Muslims - Idrus, Husni; M, M. Galib; Aderus, Andi; Ibrahim, Sulaiman (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study is motivated by the need to understand the role of the spiritual values of Surah Al-Ma'un in strengthening social solidarity among the Muslim community in Gorontalo, which has not been comprehensively explored. The research aims to identify how the values of the Qur'an influence social mindsets and behaviors through mosque-based charitable movements. Using the Tafsir Ijtima'i method and a socio-psychological approach, this study analyzes the social transformations driven by the implementation of four key principles of Surah Al-Ma'un: concern for people with low incomes, the importance of sharing, empathy, and social responsibility. Data were collected through in-depth interviews, participatory observations, and surveys involving members and beneficiaries of charitable movements from 340 mosques in Gorontalo. The findings reveal that 70% of mosques provide fod for Friday prayer congregations through donation-based funding, significantly contributing to poverty alleviation and reducing social inequality. These findings also show that the charitable movements inspire value transformation, balancing individual and social piety (At-Tawazun) and reshaping the paradigm of sharing happiness (At-Tabadul). By emphasizing the theological foundation of